Attitude of Farmers towards Mixed Farming - V. T. Onima , N. B. Chauhan and Krunal D. Gulkari, (Indian Journal of Extension Education, 2017)
The mixed farming through combination of crop production and their complementary livestock enterprises certainlycreate great potential of farms, establishing a complementary relationship between crop and livestock enterprises. Todevelop agriculture as a whole, economic condition of farmers is one of the important issues to analyze in popularizing useof mixed farming for agricultural development; there is a need to understand existing perception of the farmers towardsrelevance of mixed farming. As attitude assist individuals in processing complex information and to make decisions, aninstrument has been developed to measure attitude of farmers towards mixed farming, for which “Scale Product Method”which combines the Thurston's Equal Appearing Interval Scale (1928) for selection of the items and Likert's SummatedRating Scale (1932) for ascertaining the response on the scale, was followed. The study was conducted on a randomsample of 50 mixed farming adopters selected from ten villages of Anand taluka, of Anand district. It was observed thatmajority (90.00 %) of the farmers had positive attitude towards mixed farming. The positivism towards mixed farmingwas observed uniformly amongst the farmers with irrespective level of their age, education, farming experience, farmsize, herd size, social participation, mass media exposure, extension contact, economic motivation and achievementorientation, while it was observed highly positive amongst the farmers with high level of scientific orientation.